The prevalence and associated factors of cigarette smoking and its association with opium use among outpatients in Afghanistan: A cross-sectional study in Andkhoy city - Hamrah, Mohammad Shoaib (Avicenna J Med, 2019)
PURPOSE: The objectives of this study were to estimate the prevalence and associated factors of cigarette smoking and the association between cigarette smoking and opium use among patients visiting an outpatient clinic in Afghanistan. METHODS: A cross-sectional study was conducted on consecutive patients aged 18 years and older from January 2018 to April 2018. Data on patients’ sociodemographic characteristics and clinical variables were collected using an interview-based survey. RESULTS: Six hundred and twenty-two patients (391males vs. 231 females) were interviewed for this study. The overall prevalence of current smoking was 50.2% (95% confidence interval [CI]: 46.2–54.2). Males were (odds ratio [OR] = 9.5; 95% CI: 5.3–17.1) more likely to smoke cigarettes than females. The odds of current cigarette smoking increased with having a family member smoker or a friend smoker (OR =3.3; 95% CI: 2.0–5.3). Cigarette smoking was significantly associated with the level of education (illiterate OR = 8.9; 95% CI: 4.0–19.8), primary/private education (OR = 7.8; 95% CI: 3.9–15.6), and secondary education (OR = 4.4; 95% CI: 2.3–8.4), with high school or higher education as the reference group. Rural residents were 3.7 times (95% CI: 2.3–6.2) more likely to smoke cigarette than urban residents. Opium users were 23.0 times (95% CI: 12.5–42.3) more likely to smoke cigarettes than non-opium users. CONCLUSIONS: The prevalence of cigarette smoking among patients visiting an outpatient clinic in Afghanistan was high, and there was an association between cigarette smoking and male gender, a family history of smoking or a friend history of smoking, level of education, rural residency, and opium consumption.